Post a New Question

algebra 2

posted by on .

solve the equation m^6 -64=0

  • algebra 2 - ,

    M^6-64=0
    M^6=64
    take 6root of M^6 to get M
    take 6root of 64 which =+or-2
    so,M=+-2

  • algebra 2 - ,

    (m^2-4)(m^4+4m^2+16) = 0
    (m+2)(m-2)(m^4+4m^2+16) = 0

    so, m = 2 and -2 are solutions

    Now we have a quadratic in m^2, so

    m^2 = [-4 +/- sqrt(-48)]/2
    = -2 +/- 4sqrt(3)i
    m = +/- 1 +/- sqrt(3)i

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question